Potential of a shopping street to serve as a food distribution center and an evacuation shelter during disasters: Case study of Kobe, Japan. (April 2020) - Kotani, Hitomu; Yokomatsu, Muneta; Ito, Hideyuki
Abstract: This study demonstrates the potential use of a shopping street with disaster-proof buildings as a temporary evacuation shelter for local residents at the time of a disaster. We propose a simple estimation method to calculate the number of people for which the retail shops and restaurants in the shopping street can potentially provide food and drink using their inventory. We also estimate the number of evacuees that can be accommodated in the vacant spaces of the buildings. Our proposed method is applied to a shopping street in Kobe, Japan. While 5, 200 people in the local community are expected to evacuate at the time of an earthquake, our survey shows that, in the case of power, gas, and water outages, the total amount of available food and drink supplied by the local shops and restaurants would be approximately 1, 200 and 1, 700 person-days, respectively. In another case, in which alternative facilities provide electricity, gas, and water, the amount of available food increases to about 2, 800 person-days. Moreover, the building can provide space for overnight stay for approximately 2, 300 people. The results also suggest that, by building stockpiles of food and drink in the unoccupied spaces of the building, the capacity of accommodating the local evacuees will be further enhanced. Future directions for more accurate and widely applicable estimation methods are also discussed.